A clinical study on the presentation and management of liver abscess in eastern Uttar Pradesh and evaluation of a low cost technique of percutaneous catheter drainage - Kumar Gupta, Amit; Kumar, Yogesh; Soni, Annanya (International Surgery Journal, 2019)
Background: The objective of the study was to assess the outcome of various modalities of treatment and evaluation of a low cost technique of percutaneous catheter drainage of liver abscess. Methods: A prospective study of patients with liver abscess was conducted in a tertiary care centre over a period of one year. Since the cost of commercially available catheter (pig tail type) for image guided percutaneous drainage of liver abscess is quite high (approx Rs 800) and considering the fact that a considerable population in eastern Uttar Pradesh is poverty stricken, this study includes an evaluation of low cost technique of percutaneous drainage of liver abscess as a pilot project. In the present study K-90 was used as “low cost drainage” and compared with pig tail catheter drainage. Results: Total 34 patients with liver abscess were enrolled in the study. 31 cases were male and 3 cases were female. 34 cases were subjected to catheter drainage (pig tail catheter, K-90) yielding varying quantities of pus from 300 ml to 2200 ml, depending on the size of the abscess. 15 out of 34 patients underwent tube drainage (K-90) by our innovative trochar cannula system using 5 mm laparoscopic metal trochar. Conclusions: Although, compared to pig tail drainage, K-90 tube drainage is associated with more number of minor complication and prolonged hospital stay, however looking to the advantages and greatly reduced cost its use is probably justified.